Roles of video games in English Language Acquisition - Hrubý, Roman (Univerzita Pardubice, 2025)
This thesis examines the potential of entertainment-based video games in promoting the acquisition of the English language. The theoretical section begins with the context of informal learning, followed by a definition of video games and a characterisation of their psychological effects on players. Finally, it discusses individual language skills and effective methods for developing them in a traditional setting. The practical part aims to answer the question of the potential of video games in the acquisition of the English language through evaluation criteria derived from the researched literature.
Role videoher v rozvoji anglického jazyka
Keywords: informální učení; videohry; motivace; ochota komunikovat; řečové dovednosti; osvojování anglického jazyka; informal learning; video games; motivation; willingness to communicate; language skills; English language acquisition